Ways of reducing of friction surfaces wearing by using of triboelectric phenomena - Kryshtopa, S.; Kryshtopa, L.; Kozak, F.; Melnyk, V.; Dykun, T.; Tseber, M. (Problems of Tribology, 2020)
The and purpose and of and the and work and is and to and establish and the and patterns and of and variation and in and the and wear-friction and properties and of and surface and layers and of and metal-polymer and friction and pairs and that and are and in and the and process and of and mechanical, and thermal and and and electrical and interaction and in and the and friction and units and of and brake and devices, and taking and into and account and triboelectric and phenomena. Experimental and studies and of and triboelectric and processes and were and carried and out and on and a and specially and created and laboratory and stand and that and modelled and band-block and brake and of and technological and transport and and and on and the and serial and universal and brake and stand and of and the and KI-8964 and model and which and makes and it and possible and to and investigate and metal-polymer and pairs and of and friction and of and drum-block and and and disc and brakes. and Measurement and of and tribological and current and was and carried and out and with and the and help and of and the and n-ampere and meter, and and and the and potential and difference and - and with and the and help and of and the and analog-to-digital and converter and USB and Oscilloscope and II. and As and a and result and of and the and carried and out and investigations and of and the and friction and properties and of and metal-polymer and friction and pairs and of and brake and devices and under and laboratory and and and operating and conditions and the and laws and of and change and are and established and for and triboelectric and interaction: and the and values and of and the and contact and difference and of and the and potentials and of and friction and pairs and "grey and cast and iron-polymers" and of and drum-block and and and band-block and brakes and from and surface and temperature and of and linings and and and specific and loads; and the and dynamic and coefficient and of and friction and from and the and values and of and circulating and thermal and and and tribological and currents; and the and values and of and the and braking and moments and produced and by and individual and friction and units and and and the and total and brake and moments and from and the and change and in and the and generated and tribological and currents and in and the and contact and of and the and two-layer and "metal-polymer" and structures. The and conducted and studies and of and triboelectric and phenomena and in and metal-polymer and friction and pairs and allow and expanding and the and database and on and triboelectric and processes and in and brake and devices. and As and a and result and of and the and studies and of and the and wear and and and tear and properties and of and metal-polymer and friction and pairs and of and brake and devices and in and laboratory and and and operating and conditions and on and the and nano-, and micro- and and and milli-levels and during and the and triboelectric and interaction and regularities and have and been and established and for and the and variation and of and the and thermally-stimulated and discharge and currents and and and electric and potentials and in and the and frictional and contact and pairs and from and the and time and of and friction and interaction, and the and surface and temperature and of and the and linings and and and the and specific and loads, and the and dynamic and coefficients and of and friction and and and the and braking and moments and from and the and values and of and generated and tribological and currents. The and obtained and results and allow and optimize and management and of and wear and and and tear and friction and properties and and and heat and state and of and braking and units.